What is a deep expert system? An analysis of first-generation limitations and a review of second-generation architectures - Keravnou-Papailiou, Elpida (My University, 1990)
First-generation expert systems have significant limitations, attributed to their not being sufficiently deep. This paper attempts to clarify the concept of deepness with respect to expert systems, by analysing the limitations of first-generation expert systems and reviewing proposed architectures for second-generation expert systems. Inherent in each architecture is a definition of deepness
Keywords: Expert systems (Computer science); Computer architecture; Computer science